Fusarium solani infection after antimicrobial treatment of a severe bacterial peritonitis: a case report and review of the literature - Intra, Jari; Sarto, Cecilia; Auricchio, Sara; Pozzi, Marco; Pieruzzi, Federico; Brambilla, Paolo (International Journal of Research in Medical Sciences, 2019)
Fungal peritonitis is a rare but serious complication of peritoneal dialysis. This infection has been reported to be mostly caused by Candida species, and less frequently by a variety of other yeasts and moulds, such as Aspergillus, Penicillium, and Fusarium spp. are commonly isolated from soil, plants and environmental surfaces, and rarely from non-immunosuppressed subjects. In this report, author describe a case of infection caused by Fusarium solani in a 59-year-old man undergoing continuous ambulatory peritoneal dialysis. The fungus was recovered from cultures of peritoneal dialysate and the pathogen identification was carried out by mass spectrometry. The patient's outcome was favorable without complications after liposomal amphotericin B treatment along with peritoneal dialysis catheter removal.